Metodologia para planejamento da expansão do setor elétrico brasileiro considerando critérios ambientais e ainteração oferta-demanda - Santos, Henrique Luz (2017)
This work presents a methodology to incorporate the environmental costs associated to the construction and operation of power plants in the long-term expansion planning process of Brazilian generation system. The Environmental Power Expansion Planning Model (or Modelo Ambiental de Planejamento da Expansão Elétrica, in Portuguese) – MAPE – is a modification of the model developed by MACHADO JUNIOR (2000) with the inclusion of the environmental costs on its objective function and the elaboration of a iterative process for considering the effect of the marginal expansion costs increase in the demand projection. Three environmental costs scenarios for Brazil are presented and the result suggests that the modifications made enhance the current methodology.